Existence and asymptotic behavior of solutions of an n-th-order differential equation partially solved with respect to derivative - Prosenyuk, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We consider a differential equation of then th order unsolved with respect to the derivative. Under certain assumptions, we investigate the existence and asymptotic behavior of solutions of this equation.